Magnetoencephalography Studies of the Envelope Following Response During Amplitude-Modulated Sweeps: Diminished Phase Synchrony in Autism Spectrum Disorder - Roberts, Timothy P. L.; Bloy, Luke; Liu, Song; Ku, Matthew; Blaskey, Lisa; Jackel, Carissa (Frontiers in Human Neuroscience, 2021)
Prevailing theories of the neural basis of at least a subset of individuals with autism spectrum disorder (ASD) include imbalance of excitatory and inhibitory neurotransmission. These circuitry imbalances are commonly probed in adults using auditory steady state responses (ASSR, driven at 40Hz) to elicit coherent electrophysiological responses (EEG/MEG) from intact circuitry. Challenges to the ASSR methodology occur during development, where the optimal ASSR driving frequency may be unknown. An alternative approach (more agnostic to driving frequency) is the amplitude modulated (AM) sweep in which the amplitude of a tone (with carrier-frequency 500Hz) is modulated as a sweep from 10Hz to 100Hz over the course of ~15seconds. Phase synchrony of evoked responses, measured via intra-trial coherence, are recorded (by EEG or MEG) as a function of frequency. We applied such AM sweep stimuli bilaterally to 40 typically-developing and 80 children with autism spectrum disorder (ASD), aged 8-12 years. Diagnoses were confirmed by DSM-5 criteria as well as ADOS observational assessment. Stimuli were presented binaurally during MEG recording and consisted of 20 AM swept stimuli (500Hz carrier; sweep 10-100Hz up and down) with a duration of ~30seconds each. Peak Intra-trial coherence values and peak response frequencies of source modeled responses (auditory cortex) were examined. Firstly, the phase synchrony, or inter-trial coherence of the auditory steady state response (ASSR) is diminished in ASD; secondly, hemispheric bias in the ASSR, observed in TD, is maintained in ASD, and thirdly, that the frequency at which the peak response is obtained varies on an individual basis, in part dependent on age, and with altered developmental trajectories in ASD vs TD. Finally, there appears an association between auditory steady state phase synchrony (taken as a proxy of neuronal circuitry integrity) and clinical assessment of language ability/impairment. We conclude: 1) that the AM sweep stimulus provides a mechanism for probing ASSR in an unbiassed fashion, during developmental maturation of peak response frequency; 2) that peak frequencies vary, in part because of developmental age and, importantly, 3) that inter-trial coherence at this peak frequency is diminished in ASD, with the degree of ITC disturbance related to clinically-assessed language impairment.